Avaliação da condição periodontal e da microbiota subgengival em adolescentes tratados ortodonticamente com aparelho fixo - Binda, Caroline Lopes (2019)
Introduction: Plaque retention around orthodontic brackets may change subgingival microbiota composition and lead to gingival inflammation and, subsequently, to destruction of supporting periodontal tissues. Objective: To evaluate and compare the periodontal health and subgingival microbial plaque composition after orthodontic treatment. Materials and Methods: 23 participants aged between 10 and 19 years who had finished orthodontic treatment were selected by means of a nonprobabilistic sampling for convenience method. Subgingival plaque samples were obtained from six index teeth (16, 11, 26, 36, 31 and 46) upon orthodontic brackets removal (T1) and after 6 months (T2), and analyzed by the Checkerboard DNA-DNA hybridization technique; in addition, the participants were submitted to clinical examination in terms of visible plaque index, gingival bleeding index, probing depth and bleeding on probing. Results: A significant reduction of periodontal clinical parameters was observed six months after brackets removal. Also at T2, a significant increase of mean counts and proportions of the bacteria C. showae, F. periodonticum, S. sanguinis, S. gordonii, C. gingivalis, A. odontolyticus I, A. naeslundii I was observed (p<.05), as well as a significant reduction of F. nucleatum (sp. vincentii), E. saburreum, S. anginosus e P. melaninogenica (p<.05), with higher frequency for bacteria from the orange complex (T1: 28.28%; T2: 27.88%). Conclusion: Periodontal health is negatively influenced by the use of fixed orthodontic appliances; however, clinical parameters tend to return to normal values after brackets removal as well as the concentration of periodontopathogenic bacteria present in subgingival plaque.